Relationship of Gross Motor Function Classification System Level with The Incidence of Epilepsy - Fujianti, Annisa; Hidayah, Nurul; Triawanti, Triawanti; Fakhrurrazy, Fakhrurrazy; Bakhriansyah, Mohammad (Berkala Kedokteran, 2024)
Epilepsy is one of the comorbidities or complications that can occur in cerebral palsy (CP) pediatric, the severity of CP can be measured using the gross motor function classification system (GMFCS) level. The aim of this study was to determine the relationship of GMFCS level with incidence of epilepsy in CP pediatric at RSUD Ulin Banjarmasin. This research used a cross – sectional method. Subjects were CP pediatric outpatients aged 2-18 years at pediatric polyclinic and medical rehabilitation installation RSUD Ulin Banjarmasin. Samples were obtained with total sampling technique during September-November 2021. Data were analyzed univariate and bivariate by Fisher’s exact test with a significance level of p <0,005. There were 33 CP pediatric who fulfilled the inclusion and exclusion criteria. The result showed that most of the patients were aged 2-5 years (63,6%), male sex (57,6%), severe GMFCS levels (75,8%) and had epilepsy (66,7%). There was a significant correlation of GMFCS level with incidence epilepsy (p=0,008, PR=3,2). It can be concluded that GMFCS level is associated with incidence epilepsy in CP pediatric at RSUD Ulin Banjarmasin.